Réponses

2014-02-19T14:24:36+01:00
A = 2 - 3 - 7
A = -1 - 7
A = - 8

B = - 1 + 12 - 4 + 7
B = 11 - 4 + 7
B = 7 + 7
B = 14

C = (-5) x (3 - (- 4))
C = (-5) x (3 + 4)
C = - 5 x 7
C = - 35

U = 5 - (3 - 5 x 6)
U = 5 - (3 - 30)
U = 5 - (-27)
U = 5 + 27
U =  32

P = 2 - 6 x  (- 3)
      5 x (-11) + 35
P = 2 - (-18)
     -55 + 35
P = 2 + 18
       - 20
P = 20/-20
P = -20/20
P = 20 x -1 / 20 x 1
P -1/1
P = -1

S = -9 - -30/5 x (-3) + (-3) x (- 5)
S = - 9 - 90/5 + 15
S = -9 x 5 / 1 x 5 - 90/5 + 15 x 5 / 1 x 5
S = -45/5 - 90/5 + 75/5
S = - 135/5 + 75/5
S = - 60/35
S = 5 x - 12 / 5 x 7
S = -12/7